Exploratory Factor Analysis (EFA) Approach For Validation of Interest Assessment Instrument for Airport Personnel in Senior High School Students Grade XII - Suryono, Wiwid; Winiasri, Linda; Rozi, Fahrur; Triyono, Agus; Fatimah, Siti (Politeknik Penerbangan Indonesia Curug, 2025)
This study aims to validate an instrument to assess interest in the airport profession among XII-grade high school students using the Exploratory Factor Analysis (EFA) approach. This research is important to assist educational institutions and the aviation industry in identifying the interests and potential of students suitable for a career in airports, especially during the transition from education to the world of work. Through EFA, this study identified the factors underlying students' interest in the airport personnel profession by distributing questionnaires to 94 12th-grade high school students. Findings from factor analysis showed several key dimensions of interest, such as skills, training, career development, and interest in the airport work environment. The results of this study provide a new understanding of the factors of interest in a career in the aviation sector and produce a valid assessment instrument to assess the interest readiness of high school students interested in a career as airport personnel.